Quality of life of patients after inguinal hernia repair - Victor Shkarban; Ivan Bulyk; Andrii Gutculiak; Oleksandr Prudnikov (Journal of Education, Health and Sport, 2022)
Introduction. Endoscopic procedures for inguinal hernia repair have become widespread. There are many methods of such treatment: transinguinal preperitoneal mesh-plasty (TIPP), TAPP, TEP, MINI (combination of TEP and TAPP). However, the most common among them are TAPP and TEP. Despite the fact that these procedures are now common in many hospitals, the choice of tactics and repair procedures for different types of inguinal hernias is still uncertain. First, it concerns the quality of life of patients.